The Influence of Tax Sanctions, Tax Dissemination, and Service Quality on Motor Vehicle Taxpayer Compliance : A Study at the Denpasar City SAMSAT Office - I Gusti Ayu Padma Widyari; Ni Luh Supadmi (Green Inflation: International Journal of Management and Strategic Business Leadership, 2025)
Tax compliance refers to the behavior and actions of taxpayers in fulfilling their tax obligations in accordance with applicable laws and regulations. High tax compliance is crucial to ensuring the smooth flow of state funding, particularly in the motor vehicle sector. This study aims to provide empirical evidence regarding the influence of tax sanctions, tax socialization, and service quality on motor vehicle taxpayer compliance in Denpasar City. The research method used was accidental sampling, with a sample size of 100 respondents determined using the Slovin formula. Data were collected through questionnaires administered to motor vehicle taxpayers, and the data obtained were analyzed using multiple linear regression analysis. The results indicate that tax sanctions, tax socialization, and service quality have a positive influence on motor vehicle taxpayer compliance in Denpasar City. Specifically, the higher the public's understanding of tax sanctions and socialization conducted by the authorities, as well as the better the quality of service provided, the higher the level of taxpayer compliance in fulfilling their tax obligations. This study also shows a strong relationship between these variables in improving tax compliance. The theoretical implications of this study indicate that attribution theory and compliance theory can empirically support the idea that external factors such as sanctions and service quality, as well as educational processes through socialization, play a significant role in improving tax compliance. The practical implications of this study provide broader insights for researchers, the government, and related parties, and serve as a useful reference for stakeholders or future researchers interested in similar topics.